2009
DOI: 10.1007/s12044-009-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

Torus quotients of homogeneous spaces of the general linear group and the standard representation of certain symmetric groups

Abstract: We give a stratification of the GIT quotient of the Grassmannian G 2,n modulo the normaliser of a maximal torus of SL n (k) with respect to the ample generator of the Picard group of G 2,n . We also prove that the flag variety GL n (k)/B n can be obtained as a GIT quotient of GL n+1 (k)/B n+1 modulo a maximal torus of SL n+1 (k) for a suitable choice of an ample line bundle on GL n+1 (k)/B n+1 .Let k be an algebraically closed field. Consider the action of a maximal torus T of SL n (k) on the Grassmannian G r,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(61 citation statements)
references
References 8 publications
0
61
0
Order By: Relevance
“…The following proposition was first proved by Kannan and Sardar, [8]. A simpler proof was given in [2].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The following proposition was first proved by Kannan and Sardar, [8]. A simpler proof was given in [2].…”
Section: Introductionmentioning
confidence: 91%
“…Here w ′ = (4,5,8,9). Since w ′ > w 4,9 , X(w ′ ) contains semistable points and hence the quotient space T \ \X(w) ss T (L(9ω 4 )) is not smooth (using 3.2).…”
Section: The Young Diagram Y (W) Ismentioning
confidence: 99%
See 2 more Smart Citations
“…In [4] and [5], the parabolic subgroups Q of G containing B for which there exists an ample line bundle L on G/Q such that the semistable points (G/Q) ss T (L) are the same as the stable points (G/Q) s T (L). In [7], when Q is a maximal parabolic subgroup of G and L = L , where is a minuscule dominant weight, it is shown that there exists unique minimal dimensional Schubert variety X(w) admitting semistable points with respect to L.…”
Section: Introductionmentioning
confidence: 99%